PENDIDIKAN DAN PELAYANAN KESEHATAN PEMERIKSAAN GULA DARAH SEWAKTU PADA LANSIA DI DESA MENGWI KECAMATAN MENGWI KABUPATEN BADUNG - Suyasa, I Nyoman Gede; Jirna, I Nyoman Nyoman Gede (Poltekkes Kemenkes Denpasar, 2025)
Increased blood glucose above normal is at risk of developing Diabetes Mellitus. Diabetes Mellitus is one of the five main chronic conditions that affect the elderly. This community service refers to Arilya's research (2022) entitled Description of blood glucose levels during menopause in Bitera Village, Gianyar District using the Point Of Care Testing (POCT) method. Based on the profile data from Mengwi Village, Mengwi District, Badung Regency, the number of elderly residents is 1310 people with details of Br Delod Bale Agung 222, Br Alangkajeng 84, Br Pengiasan 98, Br. Lebah Pangkung 134, Br. Serangan 93, Br. Peregae 118, Br Pande 179, Br. Pandean 33, Br. Munggu 135, Br Gambang 105 and Br. Batu 109. The elderly's weekly activities are in the form of gymnastics. Based on the identification of the problems above, the priority of problems that need to be solved are random blood sugar examinations in the elderly and health education for the elderly for the prevention of DMThe community service method is to provide health education on the prevention of DM in the elderly with a lecture method using booklet media. Initial examination of random blood glucose for traders in the market environment using the POCT (Point of Care Testing) Method, this method is widely used because it is easy and practical, the results of blood glucose examinations can also be known in seconds and require a small sample.This community service activity will be carried out within five months, starting from the collection of initial data, health education on the prevention of DM, random blood sugar examinations and activity evaluations. The output of community service is one article in print/electronic mass media, activity videos; and increasing partner empowerment according to the problems faced, Intellectual property rights in the form of booklet media with a target achievement of 2024.The results of health services for random blood sugar examinations in the elderly ≤ 200 as many as 75 people (93.7%) more than 200 mg/dl as many as 5 people 6.3% with a high category. The output achieved is in the form of publication in the national newspaper, namely the Fajar Bali Newspaper which was published on May 20, 2024 in print and online versions with the address: https://fajarbali.com/pemerikasaan-gula-darah-sewaktu-bagi-lansia-fokus-pkm-dosen-polkesden-di-mengwi/. The next output is in the form of a video of community service activities in Mengwi Village, Mengwi District, Badung Regency with the address; https://www.youtube.com/watch?v=DsdZVhMZn8w